Rawls' Theory of International Justice: A Brief Reconstruction and Critical Commentary (Actual Problems of Mind, 2022)
The aim of this paper is to offer a concise and faithful account of Rawls’ theory of international justice, in an effort, first, to elucidate the structure of the argument that is advanced in that theory and, second, to present a critical assessment of it. The critical assessment section attempts, on the one side, to cope with crucial methodological issues, which have a more general bearing upon Rawls’ overall political philosophical position, including the constructivist perspective of theory making and the division between a political conception and a comprehensive doctrine; on the other side, to weigh up a set of substantive claims made in the Rawlsian theory of international justice, including the recognition of peoples as the fundamental subjects of international law, the toleration of the so-called decent peoples and the considerably thin construal of human rights encompassed in The Law of Peoples. The paper attempts to provide a series of reasons that could be well-suited to explicate its author’s doubts about the soundness of the Rawlsian theoretical perspective with regard to both its formal methodological features and its more content-oriented convictions.
Keywords: Political Philosophy; Philosophy of Right; Rawls; Democratic Theory